Desain Alat Peraga Digital Image Creator For Optical Microscope (DIGICOM) dalam Pembelajaran IPA untuk Menumbuhkan Motivasi Belajar Siswa - Alvian, Alvian; Yulianto, Agus; Subali, Bambang (UPEJ Unnes Physics Education Journal, 2017)
Physical learning in schools is still teacher-centered without involving students’s role actively. Especially without supported by props of physics experiment in microscope’s optical instrument learning, make student uninterested and enthusiastic when following the lessons. The purpose of this work is to design props Digital Image Creator for Optical Microscope (Digicom) and to know its influence to student learning motivation. This work uses pre-experimental method with One-Shot Case Study design. The class is chosen purposively for a treatment. To find out the feasibility of design of props Digicom used feasibility test sheet by media expert, while data of student learning motivation got from questionnaire. Based on the results of this work, the percentage of feasibility test from media experts is 80% included in the criteria worthy. The average of questionnaire result of student learning motivation is 83,4% with very high criterion. Based on the results of research can be concluded that the design of props Digicom developed feasible use in learning and able to enhance student learning motivation.